Imprefeições e Competição no Mercado Político - Melo, J. M. Vaz Marta de Sampaio e (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2005)
Public choice theory or rational politics differ from other approaches to the study of political behaviour since it supports on models in which rational individuals seek to promote their personal interests. This essay analyses the main models that adopt this political behaviour.